The Terminology Of Khulud In The Quran From The Perspective Of Imam Zamakhsari In Tafsir Al-Kassyaf - Lukmanul Hakim; Ahmad Zuhri; Harahap, Mardian Idris; Sitanggang, Cokro Malik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The scholars of tafsir have differences in the interpretation of the terminology of Khulud Hell in the Qur'an. The differences are quite striking, especially related to the verses that discuss the khulud Hell. This is what makes this research conducted. This study uses qualitative research, which involves the use of descriptive data. The maudhu'i interpretation method is used because the Mauḍu'i interpretation technique combines related verses on Qur'anic issues and has the same purpose. Data collection is done by searching and collecting verses, both related to the theme of Makiyyah and Madaniyyah in accordance with the conditions of the object. Researchers understand the relationship between verses, or munāsabat verses, both between verses and between verses and letters studied. Data analysis is inductive / qualitative, and the findings show that interpretation of meaning is more important than generalization. The results show that Al-Zamakhshari considers and strongly criticizes the opinion of Ahlussunnah that people who commit major sins may get forgiveness without repenting, as well as the opinion of Ahlussunnah that people who commit major sins will not remain in hell. From Zamakhshari's explanation in the interpretation of Surah Al-Nisa' (4):93, this verse has a general scope that applies to both believers and disbelievers. If someone kills a Muslim, it does not matter whether he is a believer or a disbeliever, and he will be in hell if he does not repent.